Dual function of IL-33 on proliferation of NIH-3T3 cells. Issue 1 (March 2015) - Tominaga, Shin-ichi; Tago, Kenji; Tsuda, Hidetoshi; Komine, Mayumi
Highlights The paper reports a novel dual effect of IL-33 on cell proliferation. IL-33 treatment suppresses initiation of cell growth of NIH-3T3 cells. The effect is not caused by apoptotic cell death.